THE IMPORTANCE OF QUALITY PUBLIC SERVICES THAT ARE FRIENDLY FOR THE SENIOR CITIZENS AND PEOPLE WITH DISABILITIES: A CASE STUDY AT THE TANAH SAREAL BOGOR DISTRICT OFFICE - Pryo Handoko (Adisam Publisher, 2024)
Service to the community has become the main goal in the implementation of public administration. Every citizen is entitled to all rights because of his or her position as an Indonesian citizen. However, it is still often found that the public facilities provided by the government do not support the accessibility of public services for the senior citizens and people with disabilities. This research is aimed at answering the questions of whether public services at the Tanah Sareal Bogor District Office are senior citizens and disabilities friendly, and what aspects should be improved so that public services can run as expected by the entire society. Data collection was carried out in addition to observation and documentation, as well as semi-structured interviews with 10 people belonging to the vulnerable society category, namely the senior citizens and people with disabilities. The results of this research indicate that public services at the Tanah Sareal Bogor District Office still need improvements to be senior citizens and people with disabilities friendly. Therefore, efforts must be done so that the missions of the Tanah Sareal Bogor District Office can be realized, namely improving the quality and integrity of human resources in services, providing professional human resources according to their field and complying with statutory provisions and increasing the professionalism of the apparatus in providing services to the society.